\[\boxed{\text{625\ (625).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[a^{2} + 8ab + 16b^{2} = (a + 4b)^{2}\]
\[Ответ:\ \ 2).\]
\[\boxed{\text{625.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[\left( 0,3x^{3} - xy^{2} \right) \cdot \ *\ =\]
\[= 0,09x^{6} - x^{2}y^{4}\]
\[\left( 0,3x^{3} - xy^{2} \right) \cdot \ *\ =\]
\[= \left( 0,3x^{3} \right)^{2} - \left( xy^{2} \right)^{2}\]
\[\left( 0,3x^{3} - xy^{2} \right)\left( 0,3x^{3} + xy^{2} \right) =\]
\[= 0,09x^{6} - x^{2}y^{4}\]
\[Надо\ умножить\ на:\]
\[0,3x^{3} + xy^{2}.\]